A Market Test for Discrimination in the English Professional Soccer Leagues - Szymanski, Stefan (Journal of Political Economy, 2000)
This paper proposes a market test for racial discrimination in salary setting in English league soccer over the period 1978–93 using a balanced panel of 39 clubs. If there is a competitive market for the services of players, the wage bill of the club will reflect their productivity and hence the performance of the club in the league. Discrimination can be said to exist if clubs fielding an above‐average proportion of black players systematically outperform clubs with a below‐average proportion of black players, after one controls for the wage bill. Statistically significant evidence of discrimination in this sense is found.